Bipolar-interface fuel cells - an underestimated membrane electrode assembly concept for PGM-free ORR catalysts - Seeberger, Dominik; McLaughlin, David; Hauenstein, Pascal; Thiele, Simon (Sustainable Energy & Fuels, 2020)
We present the first combination of a bipolar interface fuel cell with a commercial Fe-N/C catalyst as an alkaline cathode and a PGM-based, acidic anode, both separated by a proton exchange membrane (PEM). This membrane electrode assembly (MEA) concept enables the employment of Fe-N/C catalysts in a less corrosive alkaline environment, while simultaneously keeping the profound advantages of the hydrogen oxidation reaction in acidic media with extremely low PGM-material requirement. We compare two different cases for the anion exchange polymer-proton exchange polymer (AEM|PEM) interface at the alkaline cathode and the acidic membrane. In one case the PEM is simply pressed against the alkaline electrode and in the other case a part of the PEM is deposited onto the alkaline electrode. We achieved power densities of about 38 mW cm−2and 210 mW cm−2respectively. This is corresponding to 2.1 W mgPt−1cm−2. Our results show, that the bipolar interface design is one of the most important factors for performance optimization in BPM fuel cells. In addition, we compared a conventional PEM fuel cell with identical Fe-N/C cathode loading to the bipolar deposition case. After a 15 hour test run the PEMFC cell showed a strongly increased overpotential at lower current densities, whereas the overpotential increase for the bipolar cell was only marginally in the same current density region. With this work we show a facile manufacturing approach that enables bipolar interface fuel cells with Fe-N/C catalysts, showing promising power densities at low total PGM-loadings.
CRIS-Team Scopus Importer:2020-05-22

Bipolar-Interface Hydrogen Fuel Cells: A Review and Perspective on Future High-Performance, Low Platinum-Group Metal Content Designs - Seeberger, Dominik; Hartert, Adrian; Mayerhöfer, Britta; Thiele, Simon (ChemElectroChem, 2021)
This Review elucidates the state-of-the-art, challenges, and future prospects for bipolar-interface-based fuel cells (BPIFCs), focusing on hydrogen-based systems. On the one side, it provides a summary of state-of-the-art design strategies for BPIFCs from different fields of application. On the other hand, it identifies the two most pivotal areas for a future understanding that particularly refer to the changed mass transport situations introduced by the bipolar fuel cell design, that is, the water management and the bipolar interface layer itself. All operation-relevant components such as the gas diffusion layers, catalyst layers, and membrane designs are discussed within the framework of these two main areas. As non-platinum-group metal (PGM) oxygen reduction is one of the key benefits of bipolar hydrogen fuel cells, a particular focus is put on this configuration. Several additional challenges that exclusively originate from non-PGM-based catalyst layers and possible mitigation approaches are discussed. One key insight is that these thick layers could take over the role of microporous layers in the future. Finally, we emphasize that there is a strong lack in both theoretical and experimental approaches that improve our understanding of the underlying processes in bipolar fuel cell designs.
CRIS-Team Scopus Importer:2021-03-26
Keywords: alkaline oxygen reduction reaction; bipolar membrane; Fe−N/C; hybrid fuel cells; PGM-free catalysts

Bipolar membrane electrode assemblies for water electrolysis - Thiele, Simon; Mayerhöfer, Britta; McLaughlin, David; Böhm, Thomas; Hegelheimer, Manuel; Seeberger, Dominik (ACS Applied Energy Materials, 2020)
We present the first analysis of a zero-gap bipolar membrane water electrolyzer fed with liquid water. Our electrolyzers feature a high-pH environment for the oxygen evolution reaction and a low-pH environment for the hydrogen evolution reaction. The advantages of proton exchange membrane water electrolysis can be combined with those of anion exchange membrane water electrolysis by including a water splitting bipolar interface. First, we develop a KOH-free anion exchange membrane electrolysis cell. The cell's alkaline anode serves as an integral building block on the path to a bipolar system. In a second step, we use this building block to investigate the cell operation characteristics of various cell configurations. We study the cell performance as the bipolar interface is shifted progressively toward the anode. A bipolar membrane with and without a water splitting catalyst resulted in cell current densities of 450 and 5 mA cm−2 at cell voltages of 2.2 V, respectively. Upon moving the bipolar interface directly between the acidic membrane and the high-pH anode, we achieved current densities of 9000 mA cm−2 at cell voltages of 2.2 V. Our study demonstrates the potential of this water electrolysis configuration, which should be adopted for further scientific studies and may show promise for future commercial water electrolysis systems.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Additive manufacturing; Aemion; Anion exchange membrane; Bipolar membrane; PH gradient; Water electrolysis; Water splitting

Fuel cell catalyst layer evaluation using a gas diffusion electrode half-cell: Oxygen reduction reaction on Fe-N-C in alkaline media - Ehelebe, Konrad; Ashraf, Talal; Hager, Simon; Seeberger, Dominik; Thiele, Simon; Cherevko, Serhiy (Electrochemistry Communications, 2020)
Anion exchange membrane fuel cells (AEMFC) are a promising technology to allow the application of non-precious metal catalysts. While many of such catalysts have been identified in numerous recent fundamental research studies, reports evaluating these catalysts in realistic AEMFC catalyst layers together with stability assessments are rare. In the present work we show that fast and reliable evaluation and optimization of Fe-N-C-based oxygen reduction reaction (ORR) catalyst layers can be achieved using a gas diffusion electrode (GDE) half-cell approach. To set a benchmark in such measurements, a commercial Pajarito Powder Fe-N-C catalyst and commercial AemionTM ionomer are used. It is demonstrated that the ORR performance can be increased significantly by fine-tuning of the ionomer activation time. Furthermore, the optimized Fe-N-C-based catalyst layer shows very high stability with no observable performance deterioration after 5000 cycles in the 0.6–1.0 V vs. RHE potential window.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Alkaline fuel cell; Alkaline ionomer; Fe-N-C; Gas diffusion electrode; Non-noble metal catalyst; Oxygen reduction reaction

High performance direct organic fuel cell using the acetone/isopropanol liquid organic hydrogen carrier system - Hauenstein, Pascal; Seeberger, Dominik; Wasserscheid, Peter; Thiele, Simon (Electrochemistry Communications, 2020)
Liquid Organic Hydrogen Carrier (LOHC) systems offer a very interesting option for hydrogen storage in the existing infrastructure for common fuels. Technically most attractive is the direct use of LOHC-bound hydrogen in a low-temperature PEM fuel cell. Here, the isopropanol/acetone LOHC system is suggested to produce electricity from a condensable liquid without CO2 emissions. A high-performance direct isopropanol fuel cell using a vaporizer and a commercial fuel cell test system is demonstrated. For the first time backpressure is used to enhance the performance. The self-fabricated GDEs combined with a Nafion composite membrane achieved a power density of 203 mW cm−2 for Isopropanol/Air operation at 300 kPa absolute and 85 °C. By increasing the operation temperature to 100 °C a peak power density of 254 mW cm−2 is achieved, exceeding the highest reported values for isopropanol fuel cells operated with air by over 80%. The observed increase in performance can be attributed to the higher reaction rate of the electrooxidation of isopropanol at the anode side during pressurized conditions and to the reduced acetone-poisoning of the Pt-Ru catalyst at elevated temperatures.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Backpressure; Direct isopropanol fuel cells; LOHC; Organic fuel cells; Temperature

Impact of catalyst loading, ionomer content, and carbon support on the performance of direct isopropanol fuel cells - Hauenstein, Pascal; Mangoufis Giasin, Iosif; Seeberger, Dominik; Wasserscheid, Peter; Mayrhofer, Karl; Katsounaros, Ioannis; Thiele, Simon (Journal of Power Sources Advances, 2021)
Liquid Organic Hydrogen Carriers (LOHC) offer a promising solution for hydrogen storage in the existing infrastructure for conventional fuels. Within this framework, the isopropanol/acetone couple as a light-LOHC system is used to generate electricity in a direct isopropanol fuel cell (DIFC). This work focuses on the impact of catalyst loading, ionomer content and catalyst support on the performance of DIFCs. We achieve a performance rise from 95 mW cm-2 to 219 mW cm-2 under air operation by increasing the anode catalyst loading from 0.5 mg cm-2 to 4 mg cm-2, which can be attributed to the increased abundance of active catalyst sites with higher loadings. In contrast, we find that the cathode loading for the oxygen reduction reaction (ORR) plays a minor role in the performance of DIFCs. Therefore, the cathode loading can be minimized to decrease the total amount of platinum-group metals and, consequently, to save cost. It was also found that an ionomer content of 30% on the anode side is optimal. Additionally, different carbon supports were investigated, where advanced high surface area carbon support showed superior performance to Vulcan with an increase of 20% in power density, motivating the development of new carbon supports for DIFCs.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 2-propanol fuel cell; Carbon support; Catalyst loading; Direct isopropanol fuel cells; Ionomer content; LOHC; Organic fuel cells

The influence of the anion exchange membrane on mass-transport limiting phenomena in bipolar interface fuel cells with Fe-N/C based cathode catalyst layers - Seeberger, Dominik; Hauenstein, Pascal; Hartert, Adrian; Thiele, Simon (RSC Advances, 2021)
Water management is a very important issue in low temperature fuel cells such as proton exchange membrane fuel cells (PEMFCs) or anion exchange membrane fuel cells. Within bipolar interface fuel cells, water management inhibits an even more critical role. The earlier work on bipolar interface fuel cells (BPIFCs), employing Fe-N/C on the cathode side for the oxygen reduction reaction (ORR) in an alkaline environment, demonstrated increased stability of the catalyst compared to the acidic environment of the conventional PEMFCs. However, for the BPIFCs, severe mass transport limitations (MTL) dramatically reduced the power output of the cell within a few hours. In the present work water transport processes are identified as the source of the observed MTL, after evaluating the performance data of BPIFCs, where the amount of directly deposited anion exchange membrane (AEM) material was varied. It can be seen that the BPIFCs with lower AEM content show an earlier onset of MTL than the cells prepared with higher AEM content. It is shown that the AEM can be used as a tool to regulate the influx rate of product water from the bipolar interface into the CCL and that flooding of the porous layers is identified as the main source of the observed MTL. This work paves the way for further development of BPIFCs using Fe-N/C at the cathode electrode, as novel cell design strategies can now focus exclusively on avoiding flooding phenomena.
CRIS-Team WoS Importer:2021-11-19